Emotions and Ethical Decision-Making in Animal Ethics Committees - Elisabeth Tjärnström; Elin M. Weber; Jan Hultgren; Helena Röcklinsberg (Animals, 2018)
Ethical evaluation of projects involving animal testing is mandatory within the EU and other countries. However, the evaluation process has been subject to criticism, e.g., that the committees are not balanced or democratic enough and that the utilitarian weighting of harm and benefit that is normally prescribed is difficult to carry out in practice. In this study, members of Swedish Animal Ethics Committees (AECs) completed a survey aiming to further investigate the decision-making process. We found that researchers and animal laypersons make significantly different ethical judgments, and hold disparate views on which ethical aspects are the most relevant. Researchers were significantly more content than laypersons with the functioning of the committees, indicating that the ethical model used suited their preferences better. We argue that in order to secure a democratic and proper ethical evaluation, the expectations of a scientific discourse must be acknowledged, while giving room for different viewpoints. Further, to fulfil the purpose of the project evaluations and meet public concern, the functions of the different AEC member categories need to be clarified. We suggest that one way of achieving a more thorough, balanced and inclusive ethical evaluation is to allow for more than one model of ethical reasoning.